Visueller Komfort und Tageslicht am Büroarbeitsplatz. Eine Felduntersuchung in neun Gebäuden - Moosmann, Cornelia (KIT Scientific Publishing, 2014)
The study contributes to the determination of parameters that influence occupant satisfaction with the daylighting of workplaces in everyday life under consideration of seasonal differences. The users’ assessments (977 questionnaires) are supplemented by an analysis of the users’ behavior that allows conclusions on the users’ needs and on their tolerance towards adverse conditions. By evaluating users’ ratings and interventions, clues for the planning of user friendly buildings can be identified.